Genetic and Epigenetic Determinants of Low Dysferlin Expression in Monocytes. Issue 8 (24th June 2014) - Gallardo, Eduard; Ankala, Arunkanth; Núñez‐Álvarez, Yaiza; Hegde, Madhuri; Diaz‐Manera, Jordi; Luna, Noemí De; Pastoret, Ana; Suelves, Mònica; Illa, Isabel
<x xml:space="preserve">Abstract</x> The study of dysferlin expression in monocytes of a cohort of 149 healthy volunteers showed an incidence of reduced levels (within the carrier range) of the protein higher than expected. However, only 2.7% of them presented a mutation in DYSF. DNA methylation was normal in all samples tested. Our results suggest that factors other than genetic or epigenetic changes can also influence dysferlin expression and that molecular analysis of DYSF must be performed to determine the carrier status of an individual. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>